A Proposed Method to Evaluate the Effect of Changing the Kerfing Parameters upon the Static Bending Behavior of Flexible Plywood Panels Cut by Laser - Condoroţeanu, Cristina-Daria; Gurău, Lidia; Coşereanu, Camelia; Georgescu, Sergiu-Valeriu (MDPI AG, 2022)
The purpose of this paper is to propose a method for testing the effect of varying the kerfing parameters, on the flexibilization of plywood panels for indoor applications. The evaluation was made by comparisons of the change in the MOE, MOR, and maximum deflection, between flexibilized and non-flexibilized specimens subjected to static bending tests based on EN 310. In order to prevent the problem of sliding from the supports occurring for the flexibilized specimens, the standard specimens were modified by adding a frame and subjecting to bending just their central rail. Framed specimens of poplar plywood, of 8 mm thick, were laser cut with a rigid central rail, taken as reference and with the flexible kerfed rail. These had lengths of the flexible area of 50, 70, 90, and 110 mm and with two dimensions of the kerfing pitch, 6 and 10 mm. Very good correlations were found for MOE, MOR, and maximum deflection with the length of the kerfed area, for both values of the kerf pitch, which proves the sensitivity of the proposed method to the changes in the input parameters. The method could further serve to mathematically model the flexibility of a kerfed plywood panel by selecting the appropriate input data.
Keywords: flexible plywood; kerfing parameters; laser cut; static bending